2019
DOI: 10.7150/ijms.35984
|View full text |Cite
|
Sign up to set email alerts
|

Protein chip and bioinformatic analyses of differentially expressed proteins involved in the effect of hydrogen-rich water on myocardial ischemia-reperfusion injury

Abstract: Background: The differentially expressed proteins (DEPs) involved in the effect of hydrogen-rich water on myocardial ischemia reperfusion injury (MIRI) and their biological processes and signaling pathway were analyzed. Methods: 20 Wistar rats were randomly and equally divided into a control and a hydrogen-rich group. Hearts were removed and fixed in a Langendorff device. The control group was perfused with K-R solution, and the hydrogen-rich water group was perfused with K-R solution + hydrogen-rich water. Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
(26 reference statements)
0
4
0
Order By: Relevance
“…The InnoScan 300 microarray scanner was used to scan the signal using the Cy3 channel (532 nm excitation frequency) to detect fluorescence. GSR‐CAA‐67 software was used to analyse the data (Li et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…The InnoScan 300 microarray scanner was used to scan the signal using the Cy3 channel (532 nm excitation frequency) to detect fluorescence. GSR‐CAA‐67 software was used to analyse the data (Li et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…In a recent study using an isolated heart model with I/R injury, perfusion with HRW resulted in a decrease in apoptosis by up-regulating the JAK-STAT and PI3K-AKT signaling pathways (Fig. 2 ) [ 44 ]. All of these ex vivo reports are comprehensively summarized in Table 4 .…”
Section: Effects Of Hydrogen Treatment On the Heart: Reports From Ex ...mentioning
confidence: 99%
“…A multicenter, open-label clinical trial showed that hydrogen/oxygen mixed gas inhalation improved disease severity and dyspnea in patients with Coronavirus disease 2019 (COVID-19) ( Guan et al, 2020 ). In addition, H 2 has an excellent therapeutic effect on inflammation, ischemia-reperfusion injury, diabetes, cancer, atherosclerosis, and other diseases ( Li et al, 2013 ; Lee et al, 2015 ; Shimada et al, 2016 ; Li et al, 2019 ). It can reduce the levels of serum Low-Density Lipoprotein Cholesterol (LDL-C) and apolipoprotein- B (Apo-B), improve the high-density lipoprotein (HDL) functions damaged by dyslipidemia ( Song et al, 2013 ), reduce the formation of neointima after vein transplantation in rats ( Sun et al, 2012 ), and decrease hypertension, angiogenesis imbalance and oxidative stress caused by placental ischemia ( Ushida et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%